Cost-Effectiveness of Breast Cancer Screening in Turkey, a Developing Country: Results from Bahcesehir Mammography Screening Project - ÖZAYDIN, AYŞE NİLÜFER (AVES PRESS LTD, 2017)
Objective: We used the results from the first three screening rounds of Bahcesehir Mammography Screening Project (BMSP), a 10-year (20092019) and the first organized population-based screening program implemented in a county of Istanbul, Turkey, to assess the potential cost-effectiveness of a population-based mammography screening program in Turkey. Materials and Methods: Two screening strategies were compared: BMSP (includes three biennial screens for women between 40-69) and Turkish National Breast Cancer Registry Program (TNBCRP) which includes no organized population-based screening. Costs were estimated using direct data from the BMSP project and the reimbursement rates of Turkish Social Security Administration. The life-years saved by BMSP were estimated using the stage distribution observed with BMSP and TNBCRP. Results: A total of 67 women (out of 7234 screened women) were diagnosed with breast cancer in BMSP. The stage distribution for AJCC stages O, I, II, III, IV was 19.4%, 50.8%, 20.9%, 7.5%, 1.5% and 4.9%, 26.6%, 44.9%, 20.8%, 2.8% with BMSP and TNBCRP, respectively. The BMSP program is expected to save 279.46 life years over TNBCRP with an additional cost of $ 677.171, which implies an incremental cost-effectiveness ratio (ICER) of $ 2.423 per saved life year. Since the ICER is smaller than the Gross Demostic Product (GDP) per capita in Turkey ($ 10.515 in 2014), BMSP program is highly cost-effective and remains cost-effective in the sensitivity analysis. Conclusion: Mammography screening may change the stage distribution of breast cancer in Turkey. Furthermore, an organized population-based screening program may be cost-effective in Turkey and in other developing countries. More research is needed to better estimate life-years saved with screening and further validate the findings of our study.
Keywords: Mammography screening; breast cancer screening Turkey; cost-effectiveness of breast cancer screening; RESOURCE COUNTRIES; RANDOMIZED-TRIALS; WOMEN; MORTALITY; SURVIVAL